Innovative Pyrolysis Reactor for Liquid Smoke, Activated Carbon, and Limestone Production - Naswir, Muhammad; Lestari, Intan; Jalius, Jalius; Natalia, Desfaur; Wibowo, Yudha Gusti (Universitas Diponegoro, 2025)
This study presents the development and application of an innovative 3-in-1 nanotechnology pyrolysis reactor designed to simultaneously produce liquid smoke, activated carbon, and limestone from locally sourced raw materials in Jambi Province, Indonesia. The multifunctional reactor combines three production processes, which are traditionally performed separately, into a single, efficient unit, addressing both economic and environmental challenges. Coal serves as the primary heat source and material for activated carbon, whereas shell waste is calcined to produce limestone. The reactor operates at temperatures exceeding 550°C to ensure optimal conversion, with a glass wool insulator replacing clay to enhance thermal efficiency. The liquid smoke undergoes further distillation to achieve purification, while residual activated carbon is chemically activated with H₃PO₄ to enhance its adsorption capacity. The experimental results demonstrate that this reactor can produce high-quality products with minimal resource wastage. This 3-in-1 pyrolysis reactor represents a sustainable, cost-effective solution for resource-limited settings, with broad potential for application in waste-to-product conversion, environmental remediation, and rural development.